The pre-emptive empire : a guide to Bush's kingdom - Landau, Saul (Pluto Press, 2003)
"The pre-emptive empire covers all the topical and controversial issues - terrorism, the war on Iraq, oil and the economy, Enron and corporate fraud, Chile and Pinochet, Cuba and Castro, Israel and the Middle East, the IMF, the environment and globalization. Dynamic and incisive, Landau brings the debate to life with humor and intelligence. His focus on the issues should be the meat of the daily headlines."--Jacket.